2020
DOI: 10.1021/acssuschemeng.0c01107
|View full text |Cite
|
Sign up to set email alerts
|

Novel Integration of Nickel Phthalocyanine/Nickel Oxide-Based Photocathodes and Copper-Encapsulated Carbon-Dot-Cosensitized Photoanodes in Tandem for a Highly Efficient Solar Cell

Abstract: A notable strategy to achieve a dramatically high power conversion efficiency (PCE) of 9.76% for a tandem photovoltaic device has been implemented by the use of a nickel phthalocyanine-tetrasulfonic acid tetrasodium salt (NiPcTs) dye-sensitized p-type nickel oxide (NiO) semiconductor-based photocathode supported over carbon (C)-fabric paired with a photoanode scaffold comprising luminescent and conducting core/shell copper@carbon dots (Cu@C-dots) anchored to cadmium sulfide (CdS) quantum dots tethered to n-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Deepa et al reported the most efficient tandem cell to date at 9.76% for a device which included a photocathode with a nickel pthalocyanine dye (NiPcTs) on NiO supported over carbon fabric. 733 The photoanode was assembled from conducting core/shell copper@carbon dots anchored to CdS quantum dots on TiO 2 and a polysulfide electrolyte was used for compatibility with the CdS. The efficiency of the photocathode half-cell was quite low (0.039%) but when incorporated into the hybrid tandem device it improved the efficiency by almost 3% compared to the photoanode device with carbon fabric alone as the counter electrode (6.69%).…”
Section: P-type Dscsmentioning
confidence: 99%
“…Deepa et al reported the most efficient tandem cell to date at 9.76% for a device which included a photocathode with a nickel pthalocyanine dye (NiPcTs) on NiO supported over carbon fabric. 733 The photoanode was assembled from conducting core/shell copper@carbon dots anchored to CdS quantum dots on TiO 2 and a polysulfide electrolyte was used for compatibility with the CdS. The efficiency of the photocathode half-cell was quite low (0.039%) but when incorporated into the hybrid tandem device it improved the efficiency by almost 3% compared to the photoanode device with carbon fabric alone as the counter electrode (6.69%).…”
Section: P-type Dscsmentioning
confidence: 99%
“…The MS curve is fitted using eq 1 C 2 = 2 ε 0 ε A 2 e N normald ( V app V fb K B T e ) where C denotes the differential capacitance of the space-charge region, ε denotes the dielectric constant of the material, ε 0 denotes the permittivity of free space, A denotes the active area, e denotes the charge of the electron, N d denotes the electron density, V app denotes the applied voltage, K B denotes the Boltzmann constant, and T denotes the temperature. The flat-band potential represents the potential that emerged as a result of the charge accumulation or depletion in a semiconductor, and therefore, it will not lead to any band bending at the interface region . The fitting parameters show a more negative flat-band potential of −1.24 V for TiON than TiO 2 , which is −1.1 V. Further, the positive slopes of tangent lines in the linear part of the curves represent the n-type behavior of the systems.…”
Section: Resultsmentioning
confidence: 99%
“…Kolay et al. synthesized Cu/CQDs core/shell nanocomposites as modifications to the TiO 2 /CdS photocathode of a solar cell . Glucose was hydrothermally reacted in a copper NO 3 solution, yielding Cu/CQDs comprising 20–60 nm Cu cores with uniform 5 nm thick graphitic CQDs coatings.…”
Section: Synthesis Methods For Cqdsmentioning
confidence: 99%
“…Kolay et al synthesized Cu/CQDs core/shell nanocomposites as modifications to the TiO 2 /CdS photocathode of a solar cell. 61 Glucose was hydrothermally reacted in a copper NO 3 solution, yielding Cu/CQDs comprising 20−60 nm Cu cores with uniform 5 nm thick graphitic CQDs coatings. The Cu nanocores exhibited localized surface plasmon resonance, which concentrated the incident photons for increased electron−hole pair formation and reduced recombination.…”
Section: Introductionmentioning
confidence: 99%